2009
DOI: 10.1590/s1516-89132009000600001
|View full text |Cite
|
Sign up to set email alerts
|

Cacao yield in different planting densities

Abstract: The effect of six planting densities on cacao yield of a commercial hybrid mixture as well as the interaction of planting densities with the years were investigated. Crop data collected over a 14-year period (1977-1990) showed that it was possible to optimise the regional cacao yields by implementing high planting densities (2500 and 1736 trees ha -1 ). This was however only true for the first half of the crop period. In the second half, low planting density (1059 trees ha-1 ) attained the best yields. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Vertical growth is usually restricted to the first jorquette (fan of branches) (Wood and Lass, 2001) Maharaj et al (2005), Souza et al (2009), among others, found that it is possible to optimize the regional cocoa yields by implementing high planting densities (1736-2500 trees ha −1 ). However, Souza et al (2009) observed plant density by year interaction where increased yields were restricted to the first half of the crop period. In the second half, a lower planting density (1059 trees ha −1 ) resulted in the best yield.…”
Section: Planting Cacaomentioning
confidence: 99%
“…Vertical growth is usually restricted to the first jorquette (fan of branches) (Wood and Lass, 2001) Maharaj et al (2005), Souza et al (2009), among others, found that it is possible to optimize the regional cocoa yields by implementing high planting densities (1736-2500 trees ha −1 ). However, Souza et al (2009) observed plant density by year interaction where increased yields were restricted to the first half of the crop period. In the second half, a lower planting density (1059 trees ha −1 ) resulted in the best yield.…”
Section: Planting Cacaomentioning
confidence: 99%
“…Frutos e sementes são também infectados com o fungo, sujeitando-os a necrose e perda do valor comercial. O controle da doença ocorre através de podas de saneamento, controle químico e uso de genótipos resistentes (Souza et al, 2009).…”
Section: Introductionunclassified
“…Remarkably few studies have explored the relationship between cocoa yield and planting density. The scarce experimental evidence indicates that cocoa yield per hectare increases with planting density (Armstrong 1976;Charles 1961;Dias et al 2000;Pacheco et al 2003;Kowal 1959;Smith 2015;Spaggiari Souza et al 2009;Mooleedhar and Lauckner 1990). Lockwood and Yin (1996) found no differences in yields in the density range evaluated.…”
Section: How Does Yield Per Hectare Change With Density?mentioning
confidence: 99%
“…In Bahia, Brazil, higher yields were obtained at higher densities in the range of 1000-5000 trees ha −1 . However, using the maximum cocoa planting density is not always possible because it also increases the incidence of diseases (Dias et al 2000;Spaggiari Souza et al 2009).…”
Section: How Does Yield Per Hectare Change With Density?mentioning
confidence: 99%
See 1 more Smart Citation